Entrapment of Stem Extracts of Cissus quadrangularis into Biodegradable Nanoparticles and its Effectiveness for Diverse Therapeutic Activities - Subhashri, S.; Vedha Hari, B.N.; Ramya Devi, D. (Asian Journal of Chemistry, 2014)
Nature has been serving as the source of medicinal plants for several decades but presently a tremendous increase in the field of ethno-botany has emerged, dealing with the therapeutic value of traditional plants. New materialization techniques have paved the way to develop nanoparticles of ethnomedicinal plant Cissus quadrangularis Linn commonly called as “Pirandai” in Tamil. C. quadrangularis L is known to possess several pharmacological activities. Plant is extracted with petroleum ether and ethanol and its active constituents were identified through GC-MS analysis. The nanoparticles were developed by incorporating the extracts with polyvinyl pyrrolidone (PVP) as encapsulating agent and optimized for various parameters to characterize and stabilize the formulation. The crude ethanolic extract and its polyvinyl pyrrolidone-nanoparticle formulation were analyzed for their anticancer efficacy against MCF-7 (breast cancer) cell lines. Antiinflammatory and antioxidant activities were studied for the crude extracts and respective nanoparticles.